Identification of the Range of Nursing Skills Used to Provide Social Support for Mothers of Preterm Infants in Neonatal Intensive Care - Shadi Eskandari; Seyedeh Nooshaz Mirhaghjou; Maryam Maleki; Abbas Mardani; Mostafa Gholami; Celia Harding (Critical Care Research and Practice)
Background. Hospitalization of preterm infants in neonatal intensive care units (NICUs) is a stressful experience for parents. Iranian NICUs do not have specified levels of care, nor do they integrate supportive methods of parent support such as family-centered care approaches. This study investigated the range and types of neonatal nursing support, as perceived by mothers of preterm infants, and its association with mothers’ satisfaction with infant care in the NICU. Methods. This is a descriptive, correlational study of mothers of preterm infants who were hospitalized in three different NICUs in Iran. A convenience sampling method was used. Data were collected using three questionnaires that identified (i) demographic information; (ii) social support available; and (iii) parent satisfaction with infant care. Results. Mothers (N = 110) generally rated the support from nurses as being moderate. Correlation analysis identified a moderate association of neonatal nurse social support domains for affirmational (r = 0.44) and concrete aid (r = 0.41), a moderately strong association for affectional support (r = 0.64), and total social support (r = 0.60) with mothers’ satisfaction. Conclusion. There were positive associations between social support from nurses and mothers’ satisfaction with the care of their infants. Therefore, planning to promote and create opportunities for neonatal nurses to support mothers in NICU is important to promote increased maternal satisfaction in infant care.